A metatheatrical commentary on the Medea of Seneca - Jonathan Lavilla de Lera (Universidad Santo Tomás, 2016)
The article focuses on some of the rhetorical aspects of tragedy in order to provide a metatheatrical reading of Seneca's Medea. To do so, it analyzes the character of Medea as playing the role of the poet's alter ego. This analysis makes the division of the plot in two levels possible: on the one hand, there is the play of the poet, i.e. the Medea of Seneca; on the other, there is the play of Medea within the play of Seneca, i.e. the play within the play. This approach should offer the reader some meaningful reflections on the rhetorical nature of the play.